(untitled) (American Journal of Interdisciplinary Research and Development, 2025)
This article analyzes the possibilities and effectiveness of using quest technologies in the process of training future primary school teachers. Quest technology is considered as an essential tool for enhancing students’ cognitive activity, developing their abilities for independent inquiry, collaboration, creative thinking, and problem-solving. The study highlights the psychological and pedagogical foundations of quest technologies, their advantages in primary education, and the methodological opportunities for integrating quests into the professional training process of future teachers.